ANALISIS MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEBERHASILAN BELAJAR SISWA PADA MATA PELAJARAN KIMIA - Arum Sugianingsih (Arfak Chem: Chemistry Education Journal, 2020)
AbstractLearning Model Problem Based Learning (PBL) is a student-centered learning model. The entire teaching and learning process is oriented to the PBL learning model to help students become independent. The application of the Problem Based Learning (PBL) model is very important to improve student learning success in chemistry subjects, using an appropriate approach, namely the scientific approach. The learning method used is classroom action research (PTK) using the Krut Lewin's PTK model, carried out through 2 cycles containing four components in each cycle, namely: planning, action, saving, and reflection. Based on the results of review articles from several studies, it is reported that the application of the Problem Based Learning model can increase student activity and learning outcomes in good categories. Application of this model students can solve problems faced at school. In addition, this model is an alternative solution to solving low student learning outcomes due to a lack of interest in learning and motivation in students in the learning process. Keywords: interest learning model, scientific, problem based learning